2014
DOI: 10.1310/sci2001-58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FES-Ambulation Training on Locomotor Function and Health-Related Quality of Life in Individuals With Spinal Cord Injury

Abstract: Background:The combination of body weight-supported gait training with functional electrical stimulation (FES) may provide the optimal stimulus for improving overground walking after spinal cord injury (SCI). This potential benefit is likely due to the combination of specificity with the maximization of muscle contractions. Objectives: To investigate the effects of 12 weeks of FES-ambulation on overground walking and health-related quality of life (HRQOL) in individuals with SCI. Methods: Six individuals (60.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Different implications thereof were mentioned, ranging from considerable baseline variability, which could not be accounted for, to limited generalizability of the results, decreased power, and the need for replication in larger samples . Seventeen studies (10%) stated a rule‐of‐thumb like justification for the choice of a particular statistical approach, mainly that nonparametric methods were used instead of parametric approaches due to the small sample size . However, no study was found where the authors provided a theoretically sound reason (eg, by referring to a simulation study, which indicates a good performance in small sample settings).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different implications thereof were mentioned, ranging from considerable baseline variability, which could not be accounted for, to limited generalizability of the results, decreased power, and the need for replication in larger samples . Seventeen studies (10%) stated a rule‐of‐thumb like justification for the choice of a particular statistical approach, mainly that nonparametric methods were used instead of parametric approaches due to the small sample size . However, no study was found where the authors provided a theoretically sound reason (eg, by referring to a simulation study, which indicates a good performance in small sample settings).…”
Section: Resultsmentioning
confidence: 99%
“…46,47 Seventeen studies (10%) stated a rule-of-thumb like justification for the choice of a particular statistical approach, mainly that nonparametric methods were used instead of parametric approaches due to the small sample size. [48][49][50][51][52][53][54][55] However, no study was found where the authors provided a theoretically sound reason (eg, by referring to a simulation study, which indicates a good performance in small sample settings).…”
Section: Statistical Methods and Mentioning Potential Problemsmentioning
confidence: 99%
“…The duration of trainings ranged from 45 to 60 minutes. The studies of Kapadia et al 39 and Sharif et al 34 used protocols with very similar FITT characteristics. Both observed improvement in gait endurance, assessed by the 6minute walk test, whereas, in the study by Sharif et al, 34 there was a tendency to increase gait speed, which was not verified by Kapadia et al 39 Considering the outcomes presented according to the ICF domains, the authors who propose combined interventions (aerobic exercise and resistance training) are more concerned with outcomes in terms of body structures and functions.…”
Section: Quality Of Studies and Outcomes According To Icfmentioning
confidence: 99%
“…These results may indicate that Physical Exercise in SCI: Systematic Review lack of muscle strength is a limiting factor for gait functionality in these individuals. Three of the included studies that involved gait training 29,34,40 found a transfer of the benefits obtained with the interventions using FES or electromechanical devices for overground gait. Studies with combined interventions, which include 2 or more types of training in the same program, have used from ergometers to resistance exercises with cables and machines.…”
mentioning
confidence: 99%
“…FES training consists of using a multiple-channel electrical stimulator controlled by a microprocessor to recruit muscles in a programmed synergistic sequence that will allow accomplishment of a specific functional movement pattern. 5 It has been used to improve voluntary walking and balance in individuals with SCI [6][7][8][9] and grasping function by stimulating the wrist and finger muscles to increase activities of daily living and quality of life. 10,11 Only few articles have reported the use of FES during wheelchair propulsion.…”
Section: Introductionmentioning
confidence: 99%